2021
DOI: 10.1002/jemt.23978
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization induced by chitosan and collagen‐based materials with fluoride for dentin coverage: Chemical and morphological analysis

Abstract: The prevention and treatment of erosive tooth wear are becoming increasingly important due to its increasing prevalence. The use of natural solutions to modify dental surfaces has become an area of research. Organic materials such as chitosan and hydrolyzed collagen may be a promising option to treat dentin. This in vitro study aimed to evaluate the influence of chitosan or hydrolyzed collagen, alone or combined with acidulated phosphate fluoride (APF) gel, on the composition and morphology of dentin after ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…When the incident x‐rays of μ‐EDXRF interact with the surface, a smaller number of x‐rays pass through this thicker layer, resulting in smaller amounts of backscattered x‐rays. Consequently, reduced Ca and P weight percentages were observed 13 . This hypothesis is supported by the SEM micrographs of enamel (Figure 7).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…When the incident x‐rays of μ‐EDXRF interact with the surface, a smaller number of x‐rays pass through this thicker layer, resulting in smaller amounts of backscattered x‐rays. Consequently, reduced Ca and P weight percentages were observed 13 . This hypothesis is supported by the SEM micrographs of enamel (Figure 7).…”
Section: Discussionsupporting
confidence: 64%
“…Consequently, reduced Ca and P weight percentages were observed. 13 This hypothesis is supported by the SEM micrographs of enamel (Figure 7).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A study revealed that chitosan forms layers on the surface, which are differently structured according to the environment: changes in pH, chitosan concentration and application time can vary the type of layers formed [36]. In dental erosion, chitosan increases the number of cross-links between collagen fibers and neutralizes MMPs, preventing collagen degradation [37]. Furthermore, under acidic conditions, the amino groups of chitosan capture hydrogen ions, resulting in an overall positive charge that makes the molecule adhesive by electrostatic forces to negatively charged surfaces, such as enamel or dentin [38].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in demineralization can be explained by the interaction of the chitosan/fluoride gel with the dentin surface and with some of the material's adhesion promoters, which form a poor covering layer that occluded and partially occluded dentin tubules. Finally, a cover that protects against erosive challenges [37].…”
Section: Discussionmentioning
confidence: 99%